Answer:
The answers are
and
.
Step-by-step explanation:
Proportions are fractions that can be made by using the given numbers, which in this case are 2, 5, 8, and 20. Let's pair each one with the other three and then simplify if possible.
First, let's begin with 2:
![\frac{2}{5} = \frac{2}{5}](https://tex.z-dn.net/?f=%5Cfrac%7B2%7D%7B5%7D%20%3D%20%5Cfrac%7B2%7D%7B5%7D)
![\frac{2}{8} = \frac{1}{4}](https://tex.z-dn.net/?f=%5Cfrac%7B2%7D%7B8%7D%20%3D%20%5Cfrac%7B1%7D%7B4%7D)
![\frac{2}{20} = \frac{1}{10}](https://tex.z-dn.net/?f=%5Cfrac%7B2%7D%7B20%7D%20%3D%20%5Cfrac%7B1%7D%7B10%7D)
Then, let's do 5:
![\frac{5}{2} = \frac{5}{2}](https://tex.z-dn.net/?f=%5Cfrac%7B5%7D%7B2%7D%20%3D%20%5Cfrac%7B5%7D%7B2%7D)
![\frac{5}{8} = \frac{5}{8}](https://tex.z-dn.net/?f=%5Cfrac%7B5%7D%7B8%7D%20%3D%20%5Cfrac%7B5%7D%7B8%7D)
![\frac{5}{20} = \frac{1}{4}](https://tex.z-dn.net/?f=%5Cfrac%7B5%7D%7B20%7D%20%3D%20%5Cfrac%7B1%7D%7B4%7D)
Note that we already have
, so we do not need to include an additional one.
Now, let us do 8:
![\frac{8}{2} = \frac{4}{1}](https://tex.z-dn.net/?f=%5Cfrac%7B8%7D%7B2%7D%20%3D%20%5Cfrac%7B4%7D%7B1%7D)
![\frac{8}{5} = \frac{8}{5}](https://tex.z-dn.net/?f=%5Cfrac%7B8%7D%7B5%7D%20%3D%20%5Cfrac%7B8%7D%7B5%7D)
![\frac{8}{20} = \frac{2}{5}](https://tex.z-dn.net/?f=%5Cfrac%7B8%7D%7B20%7D%20%3D%20%5Cfrac%7B2%7D%7B5%7D)
See how we already have
, so we won't have to include that as well.
Finally, let's do 20:
![\frac{20}{2} = \frac{10}{1}](https://tex.z-dn.net/?f=%5Cfrac%7B20%7D%7B2%7D%20%3D%20%5Cfrac%7B10%7D%7B1%7D)
![\frac{20}{5} = \frac{4}{1}](https://tex.z-dn.net/?f=%5Cfrac%7B20%7D%7B5%7D%20%3D%20%5Cfrac%7B4%7D%7B1%7D)
![\frac{20}{8} = \frac{5}{2}](https://tex.z-dn.net/?f=%5Cfrac%7B20%7D%7B8%7D%20%3D%20%5Cfrac%7B5%7D%7B2%7D)
Now see that we already have both
and
, so we won't have to include both of them, as they are both extras.
Hence, the answers are
and
.
<h2><u><em>
PLEASE MARK AS BRAINLIEST!!!!!</em></u></h2>
Answer:
![x=-3,4](https://tex.z-dn.net/?f=x%3D-3%2C4)
Step-by-step explanation:
Factorise in order to reveal factors.
![x^2-x-12=0\\(x-4)(x+3)=0](https://tex.z-dn.net/?f=x%5E2-x-12%3D0%5C%5C%28x-4%29%28x%2B3%29%3D0)
Answer:
![y(x)=c_1e^{2ix}+c_2e^{-2ix}](https://tex.z-dn.net/?f=y%28x%29%3Dc_1e%5E%7B2ix%7D%2Bc_2e%5E%7B-2ix%7D)
Step-by-step explanation:
You have the following differential equation:
(1)
In order to find the solution to the equation, you can use the method of the characteristic polynomial.
The characteristic polynomial of the given differential equation is:
![3m^2+12=0\\\\m^2=-\frac{12}{3}=-4\\\\m_{1,2}=\pm2\sqrt{-1}=\pm2i](https://tex.z-dn.net/?f=3m%5E2%2B12%3D0%5C%5C%5C%5Cm%5E2%3D-%5Cfrac%7B12%7D%7B3%7D%3D-4%5C%5C%5C%5Cm_%7B1%2C2%7D%3D%5Cpm2%5Csqrt%7B-1%7D%3D%5Cpm2i)
The solution of the differential equation is:
(2)
where m1 and m2 are the roots of the characteristic polynomial.
You replace the values obtained for m1 and m2 in the equation (2). Then, the solution to the differential equation is:
![y(x)=c_1e^{2ix}+c_2e^{-2ix}](https://tex.z-dn.net/?f=y%28x%29%3Dc_1e%5E%7B2ix%7D%2Bc_2e%5E%7B-2ix%7D)
Answer: MARK BRAINLIEST
23x
Step-by-step explanation:
x^3+x^2+5x+5 = 23x
Answer:
y = 2
Step-by-step explanation:
6y - 2(y + 1) = 3(y - 2) + 6
6y - 2y - 2 = 3y - 6 + 6
6y - 2y - 2 = 3y
4y - 2 = 3y
4y - 2 + 2 = 3y + 2
4y = 3y + 2
4y - 3y = 3y - 3y + 2
y = 2